Analisis Pengalaman Membaca Alternative Universe (AU) sebagai Pemenuhan Kebutuhan Informasi - Putri Nova Purnama; Laksamini Laksamini (JSHP : Jurnal Sosial Humaniora dan Pendidikan, 2026)
The phenomenon of Alternative universe (AU) has become a popular movement among fans. The purpose of this study was to explore and understand the reading experiences of AU readers in meeting their needs. A qualitative research method with a phenomenological approach was employed. This study adopted an interpretative-intersubjective paradigm that focused on the construction of meaning through social reality. The reading experiences of AU were examined with five informants consisting of high school students and office workers aged 15-30 years. The findings of this study indicate that reading AU has gained popularity during the Covid-19 pandemic as a means to fulfill the information and entertainment needs of individuals who feel bored and fatigued. The use of social media platforms such as Twitter, Ask.fm, Wattpad, AO3, and AsianFanfiction, along with creative visual elements, has played a significant role in the increasing phenomenon of reading AU. The phenomenological approach provides a comprehensive understanding of the AU reading experience, with individuals attributing subjective meanings based on self-identification. Furthermore, the writing style, author's perspective, and shared preferences between fans and idols also play essential roles in the AU reading experience.